Evaluating dental health in patients with different severity of Parkinson’s disease: a cross-sectional study - Ziyu Ge; Jing Chen; Xinhui Chen; Rundong Zhang; Yanzhen Zhang; Wei Luo (BMC Oral Health)
Abstract Background/objectives Parkinson’s disease (PD) patients appear to have an increased risk of developing dental disease. This study aimed to evaluate the status of the dental caries, oral hygiene and periodontal health among a group of Chinese PD patients with different disease severity. Methods A total of 424 PD patients were enrolled in the study. The Movement Disorder Society Unified Parkinson’s Disease Rating Scale (MDS-UPDRS) and Modified Hoehn and Yahr scale (HY) were used to assess PD symptoms and severity. The Decayed, Missing, and Filled Teeth index (DMFT), Community Periodontal Index for Treatment Needs (CPITN) and Simplified Oral Hygiene Index (OHI-S) were used to assess dental status. Multiple linear, binary logistic and ordinal logistic regression estimated the association between PD parameters and dental parameters. Results More advanced PD stage was associated with worse periodontal health (β = 0.771, p < 0.001). More advanced PD motor impairment was associated with increased number of untreated caries (β = 0.066, p < 0.001), poorer oral hygiene (β = 0.030, p < 0.001) and periodontal status (β = 0.040, p < 0.001). Increased difficulties in chewing and swallowing were experienced in PD patients with more decayed teeth (rho = 0.218, p < 0.00019). Conclusions After considering the influence of age, gender, civil status, years of education and place of residence, the findings from the present study suggested that poorer oral health was observed in more advanced staged PD patients. The findings underscore the importance of integrating oral care into the overall management of PD. Clinical trial number Not applicable.